Human impacts on George River Caribou: An Overview - Harrington, Fred H. (Rangifer, 1996)
Habitat loss exerts its influence by lowering the carrying capacity of the habitat. Loss of critical habitat, therefore, is of most concern. The fact that calving range is the one "constant" in the caribou's migratory movements, and that summer range appears to be overgrazed at present and may be limiting the population, indicates that protection of habitat in or about calving and summer range is a priority. It is important to monitor human influences of the population, so that changes in the relative magnitudes, at least, of these variables can be detected before their impacts become serious. Until a fuller understanding of the impacts of these various activities is acquired, it may be more appropriate to accept the alternative hypothesis that there is an impact, rather than the null hypothesis that there is none.